PRAKTIKALITAS PERANGKAT EKSPERIMEN TEORI KINETIK GAS UNTUK FISIKA SEKOLAH MENENGAH ATAS - Sugianto '; M. Nor '; Zulhelmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to test the experiment equipment practicability of gas kinetic theory that consist of experiment tools and the escort book of experiment tools utilizing. The approach used in this study is Research and Development with 4D Model. The data obtained from practicability questionnaire. The respondent were from teachers and students that acted as user. The data was analyzed uding Ms. Excel. The practicability score test by students and teachers been categorize in high and very high. This study result indicate that the experiment equipment of gas kinetic theory is serve the purpose of physics learning media in school.Keyword : practicality test, experiment equipment, 4D Model